-22=-2+6(-2x+22)

Simple and best practice solution for -22=-2+6(-2x+22) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -22=-2+6(-2x+22) equation:



-22=-2+6(-2x+22)
We move all terms to the left:
-22-(-2+6(-2x+22))=0
We calculate terms in parentheses: -(-2+6(-2x+22)), so:
-2+6(-2x+22)
determiningTheFunctionDomain 6(-2x+22)-2
We multiply parentheses
-12x+132-2
We add all the numbers together, and all the variables
-12x+130
Back to the equation:
-(-12x+130)
We get rid of parentheses
12x-130-22=0
We add all the numbers together, and all the variables
12x-152=0
We move all terms containing x to the left, all other terms to the right
12x=152
x=152/12
x=12+2/3

See similar equations:

| 4(4x+1)=3x-4(6-×)+8 | | 3.14×r^2=706.5 | | 4/7y-5=23 | | (3.14)(r^2)=706.5 | | 26÷k=2 | | -5+9(x+6)=-(x-8)+6 | | 6-8x=-266 | | F(x)=(x-2)3=6 | | 3x+17=6x+6 | | Y=-2x+6x+1 | | 3x+14=-6x+14 | | 3x+12=(x+6) | | (3x+12)=x+6 | | 1(x-2)-6=-3(x+3) | | -17h+-7h+20h+-3=-15 | | 12+n=4n-6 | | 19s+s-16s=8 | | 45m=5 | | (24+2x)(18+2x)=1512 | | -m+19m+-7m=-11 | | 4b^2-12b=0 | | (3x+11)+(8x+2)=90 | | 6t+2t-7t=2 | | 7x+185=360 | | 4a+10=a-5 | | -6y+-8y+-12=16 | | 3x+118x+2=90 | | 7t+t+3t-7t-t=9 | | 3k-11=-5 | | 12b-7b-4b=6 | | K-4=10-k | | 4s^2-4s=1 |

Equations solver categories